2021
DOI: 10.1111/ele.13817
|View full text |Cite
|
Sign up to set email alerts
|

A general theory of avian migratory connectivity

Abstract: Birds exhibit a remarkable array of seasonal migrations. Despite much research describing migratory behaviour, the underlying forces driving how a species’ breeding and wintering populations redistribute each year, that is, migratory connectivity, remain largely unknown. Here, we test the hypothesis that birds migrate in a way that minimises energy expenditure while considering intraspecific competition for energy acquisition, by developing a modelling framework that simulates an optimal redistribution of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 54 publications
3
41
0
Order By: Relevance
“…Recently, Somveille et al (2021) developed a closely related model for inferring migratory connectivity from breeding and non-breeding distributions and cost-based estimation. Two key differences are that: (1) BirdFlow models the entire track X 1 , .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Somveille et al (2021) developed a closely related model for inferring migratory connectivity from breeding and non-breeding distributions and cost-based estimation. Two key differences are that: (1) BirdFlow models the entire track X 1 , .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Somveille et al (2021) developed a closely related model for inferring migratory connectivity from breeding and non-breeding distributions and cost-based estimation. Two key differences are that: (1) B ird F low models the entire track X 1 ,…, X T instead of just the starting and ending locations, (2) B ird F low incorporates entropy regularization to combat problems that arise with exact cost minimization, including too little variability in inferred routes (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, geographic barriers alter the energetic cost of habitat selection and, thus, the net energy availability of a given location Somveille et al, 2021). In addition, competition from residents may reduce the energy available to migrants, further weakening the expected relationship between what amounts to a subset of the species assemblage and primary productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have identified some geographical and bio-energetic conditions that affect the strength of avian migratory connectivity (Finch et al 2018;Somveille et al 2021), the underlying ecoevolutionary drivers are poorly understood. In particular, no interspecific comparative analysis has been conducted, though such analysis would be essential to disentangle the potential evolutionary and ecological drivers of the extent of migratory connectivity in different species.…”
Section: Introductionmentioning
confidence: 99%